Good Hand Hygiene Practices: Increasing Public Awareness through Policy and Public Campaigns - Dedianto, Dedianto; Sukrisyanto, Agus (Formosa Journal of Science and Technology, 2024)
This descriptive quantitative research evaluates compliance with and perceptions of hand hygiene practices among healthcare workers in hospitals in the city of Prabumulih and in the district of Muara Enim. Employing a simple random sample, 115 healthcare professionals were surveyed using a questionnaire based on the Health Belief Model (HBM) administered via Google Forms. The study primarily focuses on various perceptions including susceptibility, severity, benefits, barriers, cues to action, and self-efficacy towards hand hygiene. Statistical analyses, both descriptive to outline the general tendencies and inferential to explore the interconnections between different HBM constructs, aim to provide insights into the factors influencing hand hygiene practices. This research underscores the critical gaps between knowledge and actual hand hygiene behavior, particularly evident among healthcare students, highlighting the need for targeted educational strategies to enhance compliance and reduce disease transmission effectively.